Musculoskeletal extremity pain in Danish school children – how often and for how long? The CHAMPS study-DK - Fuglkjær, Signe (BMC Musculoskelet Disord, 2017)
BACKGROUND: Musculoskeletal pain is common in childhood and adolescence, and may be long-lasting and recurrent. Musculoskeletal problems tend to follow adolescents into adulthood, and therefore it is important to design better prevention strategies and early effective treatment. To this end, we need in-depth knowledge about the epidemiology of musculoskeletal extremity problems in this age group, and therefore, the aim of this study was to determine the prevalence, frequency and course of musculoskeletal pain in the upper and lower extremities in a cohort of Danish school children aged 8–14 years at baseline. METHODS: This was a prospective 3-year school-based cohort study, with information about musculoskeletal pain collected in two ways. Parents answered weekly mobile phone text messages about the presence or absence of musculoskeletal pain in their children, and a clinical consultation was performed in a subset of the children. RESULTS: We found that approximately half the children had lower extremity pain every study year. This pain lasted on average for 8 weeks out of a study year, and the children had on average two and a half episodes per study year. Approximately one quarter of the children had upper extremity pain every study year that lasted on average 3 weeks during a study year, with one and a half episodes being the average. In general, there were more non-traumatic pain episodes compared with traumatic episodes in the lower extremities, whereas the opposite was true in the upper extremities. The most common anatomical pain sites were ‘knee’ and ‘ankle/ft’. CONCLUSION: Lower extremity pain among children and adolescents is common, recurrent and most often of non-traumatic origin. Upper extremity pain is less common, with fewer and shorter episodes, and usually with a traumatic onset. Girls more frequently reported upper extremity pain, whereas there was no sex-related difference in the lower extremities. The most frequently reported locations were ‘knee’ and ‘ankle/ft’. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12891-017-1859-8) contains supplementary material, which is available to authorized users.